Discovery and validation of plasma proteomic biomarkers relating to brain amyloid burden by SOMAscan assay. Issue 11 (5th September 2019) - Shi, Liu; Westwood, Sarah; Baird, Alison L.; Winchester, Laura; Dobricic, Valerija; Kilpert, Fabian; Hong, Shengjun; Franke, Andre; Hye, Abdul; Ashton, Nicholas J.; Morgan, Angharad R.; Bos, Isabelle; et al.
Abstract: Introduction: Plasma proteins have been widely studied as candidate biomarkers to predict brain amyloid deposition to increase recruitment efficiency in secondary prevention clinical trials for Alzheimer's disease. Most such biomarker studies are targeted to specific proteins or are biased toward high abundant proteins. Methods: 4001 plasma proteins were measured in two groups of participants (discovery group = 516, replication group = 365) selected from the European Medical Information Framework for Alzheimer's disease Multimodal Biomarker Discovery study, all of whom had measures of amyloid. Results: A panel of proteins (n = 44), along with age and apolipoprotein E ( APOE ) ε4, predicted brain amyloid deposition with good performance in both the discovery group (area under the curve = 0.78) and the replication group (area under the curve = 0.68). Furthermore, a causal relationship between amyloid and tau was confirmed by Mendelian randomization. Discussion: The results suggest that high‐dimensional plasma protein testing could be a useful and reproducible approach for measuring brain amyloid deposition.